Adsorption of Nickel Ions on Oxygen-Functionalized Carbons - Kern, Andreas; Zierath, Bodo; Fey, Tobias; Etzold, Bastian (Chemical Engineering & Technology, 2016)
The adsorption of nickel(II) ions on pristine and wet-chemically oxidized microporous carbons is studied. The nature and acidity of the resulting oxygen functional groups are characterized by temperature-programmed desorption and point of zero charge measurements. The maximal nickel ion adsorption capacity of the resulting high-affinity Langmuir-type adsorption equilibrium is strongly influenced by the oxidative pretreatment. At maximum, loadings of 7.5 wt % could be obtained for carbons showing oxygen content of 12.5 mmol g−1. A linear correlation of the ion uptake with the surface oxygen content could be deduced. In a kinetic study, it could be proved that the uptake of nickel at room temperature is a slow process and that the time for adsorption is independent of oxygen content, carbon type, and nickel loading. <br
Keywords: Oxygen-functionalized carbons; Surface treatment; Ion adsorption; Nickel adsorption; Carbide-derived carbon

An advanced method to manufacture hierarchically structured carbide-derived carbon monoliths - Fey, Tobias; Zierath, Bodo; Kern, Andreas; Greil, Peter; Etzold, Bastian (Carbon, 2014)
The preparation of carbide-derived carbon (CDC) monoliths with a hierarchically structure in the mu m and pm range is presented. Basis is the manufacturing of porous cellular SiC ceramics based on a biomorphous approach with pm porosity and subsequent conformal conversion to CDC by reactive extraction with chlorine. The SiC ceramics can be sintered at low temperatures and short times (1500 degrees C, 2 h) compared to classical preparation methods. The SiC ceramics show a macro pore volume (1-10 mu m channel size) of 0.56 ml g(-1), which corresponds to 1.5 ml g(-1) in the resulting CDC. The final carbon material exhibits an additional nano pore volume of 0.525 ml g(-1) with a mean slit pore size of 0.86 nm. Mechanical stabilities of the highly porous CDC are excellent (bending strength 2.1 +/- 0.2 MPa, corrected Weibull modulus 8.7, characteristic strength 2.2 MPa and Youngs modulus 10.0 +/- 0.5 GPa). The reactive extraction of the carbide monoliths shows very high reaction rates, approx. two dimensions faster (95x) compared to non-porous samples. Thus the manufacturing of the structured carbide and CDC can be performed at lower costs. (C) 2013 Elsevier Ltd. All rights reserved.

Carbide-derived carbon with hollow core structure and its performance as catalyst support for methanol electro-oxidation - Ariyanto, Teguh; Kern, Andreas; Etzold, Bastian; Zhang, Guirong (Electrochemistry Communications, 2017)
New hollow core particles of mesoporous/graphitic carbon were successfully prepared from carbon core-shell particles, through selective removal of the core. Electrocatalysts prepared by dispersing platinum on these hollow core materials showed remarkably high dispersion. The combination of high dispersion with short pore diffusion length allowed to obtain high mass specific activity in methanol electro-oxidation (ca. 390 A gPt − 1), along with excellent long-term stability. These novel carbon nanostructures show great promise as Pt catalyst support for methanol oxidation.
CRIS-Team Scopus Importer:2023-08-15
Keywords: Carbide-derived carbon; Fuel cells; Hollow core particles; Methanol electro-oxidation; Pt electrocatalysts

High selectivity of TiC-CDC for CO2/N2 separation - Silvestre-Albero, Ana; Rico-Frances, Soledad; Rodriguez-Reinoso, Francisco; Kern, Andreas; Klumpp, Michael; Etzold, Bastian; Silvestre-Albero, Joaquin (Carbon, 2013)
A series of carbide-derived carbons (CDC) have been prepared starting from TiC and using different chlorine treatment temperatures (500–1200 °C). Contrary to N2 adsorption measurements at -196 °C, CO2 adsorption measurements at room temperature and high pressure (up to 1 MPa) together with immersion calorimetry measurements into dichloromethane suggest that the synthesized CDC exhibit a similar porous structure, in terms of narrow pore volume, independently of the temperature of the reactive extraction treatment used (samples synthesized below 1000 °C). Apparently, these carbide-derived carbons exhibit narrow constrictions were CO2 adsorption under standard conditions (0 °C and atmospheric pressure) is kinetically restricted. The same accounts for a slightly larger molecule as N2 at a lower adsorption temperature (-196 °C), i.e. textural parameters obtained from N2 adsorption measurements on CDC must be underestimated. Furthermore, here we show experimentally that nitrogen exhibits an unusual behavior, poor affinity, on these carbide-derived carbons. CH4 with a slightly larger diameter (0.39 nm) is able to partially access the inner porous structure whereas N2, with a slightly smaller diameter (0.36 nm), does not. Consequently, these CDC can be envisaged as excellent sorbent for selective CO2 capture in flue-gas streams.
EAM Import::2019-03-13

Improving control of carbide-derived carbon microstructure by immobilization of a transition-metal catalyst within the shell of carbide/carbon core shell structures - Ariyanto, Teguh; Gläsel, Jan; Kern, Andreas; Zhang, Guirong; Etzold, Bastian (Beilstein Journal of Nanotechnology, 2019)
Carbon materials for electrical energy devices, such as battery electrodes or fuel-cell catalysts, require the combination of the contradicting properties of graphitic microstructure and porosity. The usage of graphitization catalysts during the synthesis of carbide-derived carbon materials results in materials that combine the required properties, but controlling the microstructure during synthesis remains a challenge. In this work, the controllability of the synthesis route is enhanced by immobilizing the transition-metal graphitization catalyst on a porous carbon shell covering the carbide precursor prior to conversion of the carbide core to carbon. The catalyst loading was varied and the influence on the final material properties was characterized by using physisorption analysis with nitrogen as well as carbon dioxide, X-ray diffraction, temperature-programmed oxidation (TPO), Raman spectroscopy, SEM and TEM. The results showed that this improved route allows one to greatly vary the crystallinity and pore structure of the resulting carbide-derived carbon materials. In this sense, the content of graphitic carbon could be varied from 10-90 wt % as estimated from TPO measurements and resulting in a specific surface area ranging from 1500 to 300 m(2)g(-1).
CRIS-Team WoS Importer:2019-02-21

Preparation of carbide-derived carbon supported platinum catalysts - Hasse, Benjamin; Gläsel, Jan; Kern, Andreas; Murzin, D. Yu.; Etzold, Bastian (Catalysis Today, 2015)
Well defined carbon supported catalysts are of interest to deduce structure activity relationships and for catalyst optimization. Carbide-derived carbons (CDC) are high purity porous carbons with tunable pore structure. The deposition of platinum on silicon and titanium carbide based CDC was studied, using a three step process of acid treatment, ion-adsorption of platinum precursor and gas phase reduction. The influence of the steps on the carbon support properties and possibility to control the platinum loading and resulting cluster size was determined. Most crucial is the acid treatment step, where oxygen groups are introduced. At a too high degree of functionalization (non-carbon content above 30 wt%), which can result for nitric acid treatment, the pore structure is heavily attacked. For sulfuric acid treatments non-carbon contents below 15 wt% and only minor changes in the pore structure were observed. The ion-adsorption technique could be successfully transferred to the CDC supports. For medium to high degrees of functionalization (non-carbon contents above 20 wt%) the full deposition of 2.5 wt% of platinum was achieved. By the choice of platinum precursor, the pH of impregnation and the temperature of reduction the platinum cluster size could be varied from 2.5 to 5.3 nm. Thus, important knowledge how to prepare tuned Pt/C catalysts based on CDC and the ion-adsorption technique could be deduced.
EAM Import::2019-03-08

Preparation of hollow mesoporous carbon spheres and their performances for electrochemical applications - Ariyanto, T.; Zhang, Guirong; Kern, Andreas; Etzold, Bastian (IOP Conference Series: Materials Science and Engineering, 2018)
Hollow carbon materials have received intensive attention for energy storage/conversion applications due to their attractive properties of high conductivity, high surface area, large void and short diffusion pathway. In this work, a novel hollow mesoporous material based on carbide-derived carbon (CDC) is presented. CDC is a new class of carbon material synthesized by the selective extraction of metals from metal carbides. With a two-stage extraction procedure of carbides with chlorine, firstly hybrid core-shell carbon particles were synthesized, i.e. mesoporous/graphitic carbon shells covering microporous/amorphous carbon cores. The amorphous cores were then selectively removed from particles by a careful oxidative treatment utilizing its low thermal characters while the more stable carbon shells remained, thus resulting hollow particles. The characterization methods (e.g. N2 sorption, Raman spectroscopy, temperature-programmed oxidation and SEM) proved the successful synthesis of the aspired material. In electric double-layer capacitor (EDLC) testing, this novel hollow core material showed a remarkable enhancement of EDLC's rate handling ability (75% at a high scan rate) with respect to an entirely solid-mesoporous material. Furthermore, as a fuel cell catalyst support the material showed higher Pt mass activity (a factor of 1.8) compared to a conventional carbon support for methanol oxidation without noticeably decreasing activity in a long-term testing. Therefore, this carbon nanostructure shows great promises as efficient electrode materials for energy storage and conversion systems.
CRIS-Team Scopus Importer:2023-08-15
Keywords: Carbide-derived carbon; Electric-double layer capacitors; Hollow carbon spheres; Methanol oxidation

Synthesis of carbon core–shell pore structures and their performance as supercapacitors - Ariyanto, Ariyanto; Dyatkin, Boris; Zhang, Guirong; Kern, Andreas; Gogotsi, Yury; Etzold, Bastian (Microporous and Mesoporous Materials, 2015)
High-power supercapacitors require excellent electrolyte mobility within the pore network and high electrical conductivity for maximum capacitance and efficiency. Achieving high power typically requires sacrificing energy densities, as the latter demands a high specific surface area and narrow porosity that impedes ion transport. We present a novel solution for this optimization problem: a nanostructured core-shell carbonaceous material that exhibits a microporous carbon core surrounded by a mesoporous, graphitic shell. Our tunable synthesis parameters yielded a structure that features either a sharp or a gradual transition between the core and shell sections. Electrochemical supercapacitor testing using organic electrolyte revealed that these novel core-shell materials outperform carbons with homogeneous pore structures. The hybrid core-shell materials showed a combination of good capacitance retention, typical for the carbon present in the shell and high specific capacitance, typical for the core material. These materials achieved power densities in excess of 40 kW kg-1 at energy densities reaching 27 Wh kg-1.
EAM Import::2019-03-12

Thermal and Electrical Conductivity of Amorphous and Graphitized Carbide-Derived Carbon Monoliths - Kern, Andreas; Zierath, Bodo; Haertle, Joachim; Fey, Tobias; Etzold, Bastian (Chemical Engineering & Technology, 2016)
The influence of graphitization and composition of carbide-derived carbon (CDC) monoliths on the electrical and thermal conductivity was investigated. Carbon monoliths with varying porosities were synthesized employing biomorphous macroporous TiC and SiC as precursors. Graphitization was carried out in situ during high-temperature chlorination with and without addition of nickel, iron, and cobalt chloride to the carbide. The graphitized monoliths showed improved properties. The results demonstrate that despite graphitic carbon also glass-like carbon, stemming from the carbide synthesis, increases the thermal and electrical conductivity significantly. <br
Keywords: Electrical conductivity; Graphitization; Carbon monoliths; Thermal conductivity